2023
DOI: 10.1002/ese3.1429
|View full text |Cite
|
Sign up to set email alerts
|

Does self‐face awareness influence green building project performance?—An empirical evidence from China

Abstract: In the circumstances of "Carbon Peak," it is imminent to implement green construction technology in the construction industry as it is a major source of CO 2 emissions. Nevertheless, little study has been done on the impact of selfface awareness (SA) on green building project performance (GP). On the basis of a large-scale questionnaire survey in China and an in-depth analysis of the four categories (cognition, behavior, satisfaction, and performance), this paper has added an SA dimension, and proposed a new i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…The variables gender, age, and professional experience appeared not to have a significant impact on the level of awareness. These findings are consistent with those of Xie et al [39] who found that gender, age, and years of experience in green building do not have significant moderating effects on the level of GB practices awareness.…”
Section: Stakeholders' Level Of Awareness Of Green Buildingssupporting
confidence: 92%
See 1 more Smart Citation
“…The variables gender, age, and professional experience appeared not to have a significant impact on the level of awareness. These findings are consistent with those of Xie et al [39] who found that gender, age, and years of experience in green building do not have significant moderating effects on the level of GB practices awareness.…”
Section: Stakeholders' Level Of Awareness Of Green Buildingssupporting
confidence: 92%
“…Table 2 reveals that stakeholders who had learned about green practices from formal training, building regulations, or demonstration projects are significantly (p < 0.05) more aware of green building than those without these sources of awareness. Novieto et al [41] and Xie et al [39] support formal training and education for raising awareness of GB practices. The development of green building demonstration projects served as learning strategies, thereby increasing GB awareness [13,42].…”
Section: Level Of Green Building Awareness and Attained Sources Of Aw...mentioning
confidence: 99%